Konsep dan Peran Teori Dalam Pembelajaran IPS di Era Globalisasi: Kajian Literatur - Saputro, Dwi (Faculty of Teacher Training and Education, University of Lampung, 2025)
This study is a Iiterature review that aims to expIore the concept and role of theory in Iearning SociaI Sciences (lPS) in the era of gIobalization. GIobalization has brought significant changes in various aspects of Iife, including education. IPS learning as one of the subjects that aims to prepare students to become good citizens and have social skills, needs to adapt to the demands of the globalization era. This study was conducted through an analysis of literature sources related to the concept of IPS learning, theoretical foundations in IPS learning, and their impIementation in the context of the globalization era. The resuIts of the study show that constructivism Iearning theory, social Iearning theory, critical theory, and contextual learning theory pIay an important roIe in deveIoping IPS Iearning that is responsive to the chaIIenges of globaIization. These theories provide a foundation for developing IPS learning that not only emphasizes factual knowledge, but also criticaI thinking skiIIs, problem-solving skills, digital literacy, collaboration, and global competence. The implications of this study are the need to develop IPS learning that is integrated with information and communication technology, oriented towards contemporary global issues, and facilitates the development of students' global competence to face challenges in the era of globalization.